Surrogate molecular markers for IGHV mutational status in chronic lymphocytic leukemia for predicting time to first treatment. Issue 8 (August 2015) - Morabito, Fortunato; Cutrona, Giovanna; Mosca, Laura; D'Anca, Marianna; Matis, Serena; Gentile, Massimo; Vigna, Ernesto; Colombo, Monica; Recchia, Anna Grazia; Bossio, Sabrina; De Stefano, Laura; Maura, Francesco; et al.
Highlights Novel surrogate markers for ZAP-70 expression in CLL are proposed. Gene expression profiling identified genes with fold-change in expression ≥ZAP-70. Supervised analysis of these gene and IGHV mutation status was performed. CRY1 and MBOAT1 may surrogate the predictive value of IGHV mutational status.